POTENSI AKTIVITAS ANTIBAKTERI FUNGI ENDOFIT DAUN PARANG ROMANG (Boehmeria virgata) (G.Forst.) Guill TERHADAP BAKTERI UJI MICROCOCCUS LUTEUS DAN BACILLUS SUBTILIS SECARA KLT-BIOAUTOGRAFI - FITRIANI, SITTI ANNISA; Kosman, Rachmat; Rusli, Rusli (Makassar Pharmaceutical Science Journal (MPSJ), 2025)
Parang romang (Boehmeria virgata (G.Forst) Guill) is a plant used to treat various infectious diseases, one of which is the digestive tract. Antibacterials are compounds that can inhibit or kill bacteria that cause infection. Endophytic fungi produce bioactive compounds in the form of antioxidants, anticancer, antiviral, antifungal and so on. This research uses the TLC-Bioatography method. The research started with the isolation of endophytic fungi and antagonist tests, which obtained active isolates against the test bacteria Micrococcus luteus and Bacillus subtilis, namely IFBV-6. Then this isolate was fermented and continued with testing using the TLC-Bioautography method. The resulting fermentate was dissolved in chloroform:methanol (5:1) solvent. Test results from TLC-Bioautography of IFBV-6 fermentate showed Rf values ​​of 0.9, 0.81 and 0.58. In the case of Micrococcus luteus and bacillus subtilis bacteria, good Rf values ​​from TLC show that there is quite good separation, ranging from 0.2-0.8, indicating clear antibacterial activity. In this test, each fermentation code has the same Rf value and number of spots. The results of identifying the chemical components of endophytic fungal isolates from parang romang leaves of Boehmeria virgata (G.Forst) Guill) gave positive results using alkaloid and saponin spotting.